An ultrastructural study of Trichophyton rubrum induced onychomycosis. Issue 1 (December 2015) - Yue, Xueping; Li, Qing; Wang, Hongwei; Sun, Yilin; Wang, Aiping; Zhang, Qi; Zhang, Cuiping
Abstract Background Trichophyton rubrum (T.rubrum ) caused onychomycosis is the most common nail fungal disease. The common diagnostic methods are direct microscopic examination and fungal culture. In this study we used scanning electron microscopy (SEM) and transmission electron microscopy (TEM) to study the subungual ultrastructural changes inT. rubrum induced onychomycosis. Methods Six outpatients with onychomycosis were recruited andT.rubrum infection was confirmed by fungal culture. Six toenail samples were collected and prepared for SEM characterization. The cultured fugal colonies were prepared for SEM and TEM characterization. Results 1) SEM showed significant structural damages and the formation of a thin layer or a single layer of keratinocytes in all infected nail plates. Hyphae (piercing or penetrating keratinocytes layers), arthrospores and local bacterial aggregation were observed on the ventral surface of the nail plates. 2) SEM of the cultured fungal colony showed relatively straight, highly branched hyphae and microconidias; TEM showed branching hyphae that were composed of double-layer cell walls. Hyphae had nucleus, mitochondria, liposomes, lysosomes, scattered rough endoplasmic reticulum, myeloid bodies and aggregated ribosomes. There were high-density particles outside the hyphae. Conclusion SEM showed a large number of hyphae penetrated the keratinocytes layer, suggesting thatT. rubrum can cause severe damage to the stratum corneum. TEM showed the ultrastructural features ofT. rubrum -induced infection before treatment.